Erratum: Characterisation of multiple carrier transport in indium nitride grown by molecular beam epitaxy [Phys. Status Solidi C 4, 2423–2427 (2007)]. Issue 2 (14th February 2013) - Fehlberg, Tamara B.; Umana‐Membreno, Gilberto A.; Gallinat, Chad S.; Koblmüller, Gregor; Bernardis, Sarah; Nener, Brett D.; Parish, Giacinta; Speck, James S.; Stanek, Christopher R.; Nikl, Martin; Kovács, László; Greulich‐Weber, Siegmund
Abstract This paper erroneously neglected to reference an earlier paper, an oversight which the authors wish to correct to improve the overall contribution of both papers. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)